Preliminary studies on the effects of using drainage water for drinking on productive traits of rabbits in Egypt - El Darawany A.A.; Farghaly H.M.; Yamani K.A.O.; Marai I.F.M. (Rabbit production in hot climates, 1994)
An investigation was carried out to study the effects of using drainage water on productive performance of commercial rabbits. The nitrate and nitrite values of drainage water were higher than the maximum permissible levels. Drinking of drainage water during pregnancy was accompanied by decrease in litter size and litter weight as days of drinking drainage water increased, while bunny weight and daily gain gradually increased by increasing of days of drinking drainage water wither during gestation or suckling period. The productive performance of does drinking drainage water for six days at the beginning of the suckling period was inferior to that of does drinking tap water. Mortality rate in the offsprings increased by increasing days of drinking drainage water during gestation or suckling period. The greatest effect of drinking drainage water on rabbits productive performance was during the suckling period.
1. International Conference of rabbit production in hot climates, 1994/09/06-08, Cairo (Egypt)